2015
DOI: 10.1186/s40748-015-0024-3
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for acute bilirubin encephalopathy on admission to two Myanmar national paediatric hospitals

Abstract: BackgroundJaundice is the commonest neonatal ailment requiring treatment. Untreated, it can lead to acute bilirubin encephalopathy (ABE), chronic bilirubin encephalopathy (CBE) or death. ABE and CBE have been largely eliminated in industrialised countries, but remain a problem of largely undocumented scale in low resource settings. As part of a quality-improvement intervention in the Neonatal Care Units of two paediatric referral hospitals in Myanmar, hospitals collected de-identified data on each neonate trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 26 publications
2
23
1
Order By: Relevance
“…3 A study conducted in Myanmar reported that neonatal jaundice was the major cause of neonatal morbidity and mortality and was responsible for 46% of hospital admission of neonates in the country. 8 In 2015, a cross sectional study was conducted in Islamabad among 200 respondents to assess the knowledge of mother regarding neonatal jaundice. The study showed that 52.5% mothers had inadequate score while 47.5% mothers had adequate knowledge score.…”
Section: Introductionmentioning
confidence: 99%
“…3 A study conducted in Myanmar reported that neonatal jaundice was the major cause of neonatal morbidity and mortality and was responsible for 46% of hospital admission of neonates in the country. 8 In 2015, a cross sectional study was conducted in Islamabad among 200 respondents to assess the knowledge of mother regarding neonatal jaundice. The study showed that 52.5% mothers had inadequate score while 47.5% mothers had adequate knowledge score.…”
Section: Introductionmentioning
confidence: 99%
“…A recent review noted the lack of empirical evidence of the efficacy of such programs in reducing the risk of severe hyperbilirubinemia, but nevertheless echoed this recommendation on the basis of the available evidence and understanding [1,9,10,31,53,56,62,63,64,65,66]. While screening of cord-blood for G6PD deficiency is of relatively low cost, the experience of the DOTYR-15 participants is that there would need to be a substantial investment in infrastructure to support universal screening programs.…”
Section: The Present and The Future In Preventing Serious Nnjmentioning
confidence: 99%
“…The importance of Rh disease varies widely with the prevalence of Rh-negative maternal status, but the issue of affordable prophylaxis is clearly a priority for many LMICs. The lack of routine maternal and neonatal blood testing in many LMICs is also a barrier, and also impacts the management of ABO incompatibility as a risk factor for serious NNJ [7,32,53,56,57,58,59]. …”
Section: The Present and The Future In Preventing Serious Nnjmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 This enzyme deficiency also contributed to 17%-36% of phototherapy needed neonatal jaundice in neonatal units of children hospitals in this country. 5 Although there is a high prevalence of this enzyme deficiency in Myanmar, most people are not aware of their G6PD status because screening of the disease is not a routine practice yet and most of the affected persons are asymptomatic. However, if G6PD deficient people are exposed to oxidative stress, acute intravascular hemolysis may occur leading to heart failure and even death, if there is no timely intervention.…”
Section: Introductionmentioning
confidence: 99%